Process intensification for 5-hydroxymethylfurfural production from sucrose in a continuous fixed-bed reactor - Tongtummachat T. (2023)
This work proposed the novel continuous production of 5-HMF from sucrose. The production was performed in a biphasic system using a mini fixed-bed reactor packed with dual ion-exchange resins (Amberlyst-21 (A21) and Amberlyst-15 (A15)) as catalyst. The primary role of each catalyst was examined to specify the suitable position in the catalyst bed, followed by the investigation of the major factors affecting the 5-HMF yield. The effects of feed concentration of sucrose, organic-to-aqueous volumetric ratio, residence time, and catalyst-bed configuration on the reaction performance were examined and optimized. The 5-HMF yield of 64.8% was achieved under the optimal conditions as follows: temperature of 120 °C, residence time of 30 min, sucrose concentration of 5 g/L, organic-to-aqueous volumetric ratio of 0.125:1, and catalyst-bed configuration of A15-A15-A21-A15. To demonstrate the stability of catalysts, the system was operated for more than 60 h of time-on-stream without any loss of 5-HMF yield. When compared to the literature, this system offered several advantages in terms of the shorter residence time, lower O:A ratio, and higher yield, demonstrating the promising capability of our proposed process.